Analisis Kinerja Lembaga Amil Zakat (LAZ) Rumah Zakat Sumatera Barat Berdasarkan Indeks Zakat Nasional (IZN) Dengan Pendekatan Dimensi Mikro - Rahmat Fauzan; Ingra Sovita (CV. ITTC INDONESIA, 2026)
This study aims to analyze the performance of the Rumah Zakat West Sumatra Amil Zakat Institution using the National Zakat Index (NZI) from the micro dimension, which includes institutional performance and zakat impact indicators. The research employs a descriptive quantitative approach with data collected through documentation and interviews, which are then analyzed based on the NZI calculation guidelines established by BAZNAS. The results show that the institutional performance indicator achieved an index value of 0.85, categorized as good performance, composed of collection (0.5), management (1), distribution (1), and reporting (1) variables. Meanwhile, the zakat impact indicator recorded an index value of 0.8, indicating a fairly optimal impact of zakat utilization on beneficiaries. This indicator is formed by welfare variables with a value of 1, modified Community Development Index variables with values of 1 and 0.75, and an independence variable with a value of 0.5. Overall, the findings indicate that the micro-dimension performance of Rumah Zakat West Sumatra is relatively optimal; however, improvements are still needed in zakat fund collection and beneficiary independence to enhance the sustainability of zakat impacts in the future.